2016
DOI: 10.1186/s12913-016-1801-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of diabetes care and health insurance coverage: a retrospective study in an outpatient academic public hospital in Switzerland

Abstract: BackgroundSocioeconomic disadvantage is associated with an increased risk of adverse diabetes outcomes. In Switzerland, a country with theoretical universal healthcare coverage, people without health insurance face barriers in accessing to and in receiving standard quality care. The Geneva University Hospitals (HUG) have implemented policies aiming at reducing these gaps. We compared quality of diabetes care and ambulatory healthcare services utilization among insured and uninsured diabetic patients.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Facilitating access has been shown to improve health outcomes: a study conducted in two immigration ‘sanctuary’ areas (San Francisco Bay; Chicago) showed no differences in clinical outcome and healthcare experiences of undocumented and documented migrants with diabetes 35. This corresponds to findings from a retrospective study in a public hospital in Geneva, Switzerland, enforcing health-equity policies 36…”
Section: Discussionsupporting
confidence: 56%
“…Facilitating access has been shown to improve health outcomes: a study conducted in two immigration ‘sanctuary’ areas (San Francisco Bay; Chicago) showed no differences in clinical outcome and healthcare experiences of undocumented and documented migrants with diabetes 35. This corresponds to findings from a retrospective study in a public hospital in Geneva, Switzerland, enforcing health-equity policies 36…”
Section: Discussionsupporting
confidence: 56%
“…Poor socioeconomic conditions (low income, poor education) have been associated with poor glycaemic control due to poor access to adequate care and poor health-seeking behaviors [18,48,87,98,99]. Increasing universal health coverage could address these problems and lead to better outcomes [100]. Factors such as food Fina Lubaki et al Diabetology & Metabolic Syndrome (2022) 14:134 insecurity and depression have been identified as mediators in the relationship between poor living conditions and glycaemic control [98].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, restricting access to the public healthcare system to vulnerable migrants entails higher global financial costs as recently shown in Germany [ 42 ]. Experiences in Switzerland and The Netherlands show that such a scheme is feasible, equitable and effective in regards to the management of chronic diseases [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%